What determines regulatory preferences?: insights from micropollutants in surface waters - Tosun, Jale; Bulian, Simon; Fleig, Andreas (Environmental science & policy, 2020)
The ever-increasing consumption of pharmaceuticals, cosmetics, detergents and food additives puts aquatic ecosystems under strain. Accordingly, respective regulation of micropollutants in surface waters is an issue that not only needs to include the perspective of public actors and producers but also that of the consumers. Complementing existing literature on public perception towards environmental policy instruments, this study investigates how consumers assess the risks related to micropollutants in surface waters and what their regulatory preferences are for addressing this issue. Drawing on original survey data for Germany, we show that respondents perceive the presence of micropollutants in surface waters to be an issue worth addressing, mostly due to environmental concerns. The majority of respondents is aware that they share some responsibility regarding increased levels of micropollutants in surface waters. Main responsibility is attributed to the industrial and agricultural sector, however. Regarding potential regulatory measures to mitigate the entry of micropollutants into surface waters, respondents prefer command-and-control over market-based instruments.
Gesehen am 09.04.2020